Peningkatan Kapasitas Digital PT Satria Tama Energi melalui Pelatihan Katalog Digital Berbasis Canva dan Heyzine - Prasetyo Yuliantoro; Muhammad Panji Kusuma Praja; Melinda BR Ginting (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance the digital capacity of PT Satria Tama Energi, a renewable energy company specializing in solar power systems, through training on interactive digital catalog development using Canva and Heyzine. Despite producing various renewable energy products, the partner faced limitations in product documentation and promotion due to the absence of an official digital catalog. The program was implemented over three months using a hybrid approach, consisting of three on-site meetings (introduction, hands-on training, and evaluation) complemented by online monitoring and feedback. Eleven participants, consisting of company executives, employees, and interns, were involved to ensure managerial support and sustainability. The training covered digital design principles, content structuring, catalog layout development, and interactive publication. The main output of this program is an official interactive digital catalog that can be accessed online and used as a professional promotional medium. In addition, the program improved participants’ skills in independently updating and managing digital catalogs. This activity supports Sustainable Development Goals (SDGs), particularly SDG 8 on decent work and economic growth and SDG 9 on industry, innovation, and infrastructure. Overall, the program successfully strengthened the partner’s promotional capacity and digital competitiveness.